Kesantunan Imperatif Teks Khotbah Jumat Ustaz Abu Ishaq Abdullah Nahar dalam Majalah Asy Syariah Edisi 107 : Kajian Pragmatik - Harista, Eva (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2016)
In particular, this study discusses the form of language politeness in the field of imperative pragmatics. As for the form of imperative politeness that is studied, which includes imperative or nonstructural forms of pragmatics. This research is a type of qualitative descriptive research. The data collection techniques in this study use library techniques, see techniques, and note. The results of the study found that there were some imperative politeness, namely in the form of imperative pragmatics found in the text of Friday sermon Ustaz Abu Ishaq Abdullah Nahar in Asy Syariah Magazine Edition 107, namely, 1) speech that contains the pragmatic imperative of command, 2) speech that implies imperative pragmatic meaning application, 3) speech which contains imperative appeal pragmatic meanings, the three utterances use particle politeness markers "Yes," 4) Speeches that contain the imperative pragmatic meaning of hope, with the "hopefully," politeness markers. with a mark of politeness "should, as appropriate."